A NEW CONTROL STRATAGY FOR SOLAR PVT- BATTERY AND DIESEL GENERATOR BASED EV CHARGING STATION - MR. B.RAJU; MR. V.SAIDULU; RAO, MR. VENKATESWAR (The journal of contemporary issues in business and government, 2017)
The main aim of this project tis solar pv-battery & diesel generator-based EV charging station. This paper employs a PV (photovoltaic), a power storage unit, a DG generator, & a grid-based EV charge station (CS) to continuously load isolated, grid-connected & DG-connect modes. This project involves an energy & electronic energy storage plant. In this project, the PI controller is changed to a Fractional Order PID (FOPID) controller in the DG set, which can regulate the tension & frequency. The charging station is primarily intended to recharge the electric car battery (EV) with a solar PV & BES range. However, the charging station is intellectually electricity coming from the grid or DG in case of an empty storage battery & of the unavailable production of Solar PV array (Diesel Generator). The electricity in the DG collection is however drawn in such a way that it frequently works with an 80 to 80 percent charge in all charging situations to achieve optimal fuel efficiency. In conjunction with the storage battery, the charger also handles the power & frequency of the generator without the mechanical speed control. In addition, the PCC (Common Coupling Point) tension synchronizes for continuous loading with grid/generator voltage. The charging station leads the automobile to the active/reactive transmission of the grid, the vehicle to its domestic & the vehicle to the transference of vehicle power in order to optimize its operating efficiency. With Mat lab/Simulink software the operation of the charging station is validated.